Fifteen-years of continuous application of organic materials improve the soil aggregation, organic carbon status and sustain the productivity of the basmati rice-wheat system - Mandi, Sunil; Shivay, Yashbir Singh; Chakraborty, Debashish; Shrivastava, Manoj; Nayak, Somanath; Baral, Kirttiranjan; Reddy, Kadapa Sreenivasa (Soil & tillage research, 2024)
The rice-wheat cropping system covers a considerable area of the Indo-Gangetic Plain zone (IGPZ) due to agro-pedological compatibility. The nutrient requirements of the rice-wheat system in an organic mode are met through locally available organic matter (OM) is a subject of investigation from the viewpoint of declining the underlying mechanisms. A long-term organic farming experiment was carried out at the research farm of ICAR-Indian Agricultural Research Institute, New Delhi, India. Locally available sources of OM’s such as Sesbania green manuring, Leucaena green leaf manuring, farmyard manure (FYM), blue-green algae, and Azotobacter were evaluated for changes in soil physico-chemical properties and crop yield response after 15 years continuous applied of OM’s. Our results indicate that treatment involving applied Sesbania green manure + farmyard manure + blue-green algae to rice + Leucaena green leaf manuring + farmyard manure + Azotobacter to wheat [SFB(R) + LFA(W)] showed a sharp decline in soil pH by 5.5%, soil electrical conductivity (EC) by 24.0%, and soil bulk density by 14.0% over the control within the 0–15 cm soil depth. While, the treatment SFB(R) + LFA(W) improved the soil large macroaggregate (>2.0 mm) by 85.0% in 0–7.5 cm, and 92.8% in 7.5–15 cm in soil depth. Similarly, the treatment SFB(R) + LFA(W) showed 3.2-, 2.8-fold higher mean weight diameter (MWD) in corresponding soil depths of 0–7.5 cm, 7.5–15 cm compared to the control. Treatment SFB(R) + LFA(W) increased in soil organic carbon (SOC) holding by 5-folds in soil large macroaggregate, 4-folds by soil small macroaggregate (2.0–0.25 mm), 5-folds by micro-aggregate (0.25–0.053 mm), and 9-folds by silt + clay fraction (<0.053 mm) than control in 0–15 cm soil depth. These observations strongly support greater carbon recalcitrance with a higher half-life in soil silt + clay fraction than in other soil fractions. Further, treatment SFB(R) + LFA(W) maintained higher SOC by 79.4% and carbon stock by 76.6% over control in 0–15 cm soil depth. These responses on soil aggregates and SOC changes translated into significant crop responses. The treatment SFB(R) + LFA(W) thus, showed correspondingly higher grain yield (5.41 Mg ha–1 and 4.69 Mg ha–1) of rice and wheat. Our study though showed on par agronomic response between low-quality OM’s and mixed-quality OM’s in 15-years. But considering the loading of SOC in the silt + clay fraction of soil, the study foresees a higher recalcitrant of SOC compared to any other soil fractions. This could well strengthen the process of soil aggregation having cascading response on other soil health-defined parameters a requisite for sustaining the rice-wheat sequence in the IGPZ. •15-year application of organic materials (OM’s) improves soil properties.•Applied mixed-quality OM’s had decreased the soil bulk density, EC, and pH.•Applied mixed-quality OM’s significantly increased the MWD and soil aggregation.•The soil small macroaggregate found a higher organic carbon holding in the plough layer.•The mixed-quality OM’s recorded a 54.78 Mg ha–1 carbon stock in the plough layer.